O Estado como agente educacional na Constituição de 1988 - Oliveira, Antonia Teresinha de (2009)
The proposition of this thesis is based on the belief that the interlacing of law, education and State will bring solution to the grievous social problems presently faced. The causes of social dissolution experienced at present by the totality of sovereign states, begin with the absence of education, as well as their inefficient conduction, and result in the huge social commotions. We understand that the Federal Constitution draws a wide educational program rhat needs implementation in ali areas of human acting within such ambitious program, we understand that it would be equally important and in accordance to the constitutional determination of efficiency and excellence in the actuation and implementation of public policies - an independent structuring of national education, aiming to specialization, efficiency, attention and not dispension, subject that constitutes a proposition de lege ferenda presented in this thesis. Considering that, in the sovereign state, it is the human element who promotes actions and practices acts in a determined territorial basis, we consider to be a function or duty of the state, to educate towards the social values of democracy in a regimen of sympathetic participation and co-existence, on bases of freedom and mutual respect. Taking into consideration, as well, that there are multifaceted aspects of human education which require urgent attention, we suggest the specialization of function with a view to the development of actions shared by the State and society. We wish to keep away from this proposal any idea that may tie education to determined and specific ideologies since education must have as target the man and the values that promote life and freedom, the respect for the public stuff, the administrative and social morality, the true ideals of citizenship. We have projected, as well, to involve, in this process, the family of the educating person, with their culture, this way composing, with the universal culture, new levels to understanding and progress. Such education, towards human values, will fight disbelief, which erodes, and disillusion, which kills, by means of the introduction of new targets and new bases for life in society